The complete mitochondrial genome of the flat bug Aradacanthia heissi (Hemiptera: Aradidae) - Shi, Aimin; Li, Hu; Bai, Xiaoshuan; Dai, Xun; Chang, Jian; Guilbert, Eric; Cai, Wanzhi (Zootaxa, 2012)
The 15528 bp long complete mitochondrial genome (mt-genome) of a flat bug, Aradacanthia heissi Bai, Zhang & Cai,was determined. The entire genome contains typical 37 genes with an A+T content of 74.7%. The gene arrangement dif-fers from that of Drosophila yakuba Burla which is considered the representative ground pattern for insect mt-genomes,as the results of inversion of tRNAIle - tRNAGln and tRNACys - tRNATrp . All protein-coding genes (PCGs) use standard initia-tion codons (methionine and isoleucine), except COI which starts with TTG. Three of the 13 PCGs harbor the incompletetermination codon. Meanwhile, opposite CG-skew tendency occurs on the nucleotide composition and codon usage andthis tendency is also reflected on the J-strand and N-strand of PCGs. All tRNAs can fold into classic clover-leaf structure,whereas the dihydrouridine (DHU) arm of tRNASer(AGN) forms a simple loop. Secondary structure models of the ribosomalRNA genes of A. heissi are predicted and similar to those proposed for other insects. The control region is located betweensrRNA and tRNAGln with 81.5% A+T content, which was the most A+T-rich region of the mt-genome and four 68 bp tan-dem repeat units were found in this region. Phylogenetic analyses of available species of Pentatomomorpha showed Ara-doidea and the Trichophora are sister groups that bolstered the mainstream hypothesis, and provide the evidence for the feasibility of mt-genome data to resolve relationships at the subfamily level in Aradidae.